Point-of-sale cigarette marketing and smoking-induced deprivation in smokers: results from a population-based survey. (December 2016) - Siahpush, Mohammad; Shaikh, Raees; Robbins, Regina; Tibbits, Melissa; Kessler, Asia; Soliman, Ghada; McCarthy, Molly; Singh, Gopal
Abstract Background Strict restrictions on outdoor cigarette marketing have resulted in increasing concentration of cigarette marketing at the point-of-sale (POS). The association between POS cigarette marketing and smoking-induced deprivation (SID) has never been studied. The aim of this study was to examine this association and how it is mediated by cravings to smoke, urges to buy cigarettes, and unplanned purchases of cigarettes. Methods Data from a telephone survey of 939 smokers were collected in Omaha, Nebraska. POS cigarette marketing was measured by asking respondents three questions about noticing pack displays, advertisements, and promotions such as cigarette price discounts within their respective neighborhoods. SID was measured with the following question: "In the last six months, has there been a time when the money you spent on cigarettes resulted in not having enough money for household essentials such as food? [yes/no]" We used structural equation modeling to examine the study aim. Results There was overwhelming evidence for an association between higher levels of POS cigarette marketing and a higher probability of SID (p < 0.001). This association was partly mediated by cravings to smoke, urges to buy cigarettes, and unplanned purchases of cigarettes during a visit to a neighborhood store (p < 0.001). Conclusion Given that POS cigarette marketing is associated with a higher probability of experiencing SID, policies that ban POS cigarette marketing might help some smokers afford essentials household items such as food more easily and thus have better standards of living.